A mechanistic understanding of ecological responses to land‐use change in headwater streams - Richard H. Walker; Annika W. Walters (Ecosphere, 2019)
Abstract Anthropogenic activities, such as oil and natural gas development (ONGD), have significantly altered the landscape. It is often challenging to identify the mechanistic processes underlying ecological responses to land‐use change (LUC). In aquatic ecosystems, alterations to habitat and food availability and water quality associated with increased LUC are key mechanistic pathways that deserve management consideration. We used structural equation modeling to evaluate how LUC associated with ONGD could influence macroinvertebrate and fish across 40 sites in six headwater streams in the Wyoming Range of the Upper Green River Basin, Wyoming. The most important mechanistic pathway varied, but responses were frequently driven by a direct effect of LUC or related to changes in food availability and water quality. Habitat complexity was the least important mechanistic pathway in our models. Our results also highlight that responses may reflect an organism's degree of habitat or resource specialization and/or sensitivity to changes in water quality. Habitat pathways were more important for habitat specialists (e.g., Mottled Sculpin, Cottus bairdii), food pathways were more important for food specialists (e.g., Colorado River Cutthroat Trout, Oncorhynchus clarki pleuriticus; Mountain Sucker, Catostomus platyrhynchus), and sensitivity to increased salinity was important for intolerant species (e.g., O. clarki, C. bairdii, and predatory macroinvertebrates). Continued identification of the specific mechanisms underlying species’ responses to increased LUC will aid in the conservation of ecologically and economically important species.